Effect of grip type, wrist motion, and resistance level on pressures within the carpal tunnel of normal wrists. Issue 4 (4th January 2014) - McGorry, Raymond W.; Fallentin, Nils; Andersen, Johan H.; Keir, Peter J.; Hansen, Torben B.; Pransky, Glenn; Lin, Jia‐Hua
ABSTRACT Elevated carpal tunnel pressure (CTP) has been associated with carpal tunnel syndrome. This study systematically evaluated the effect of wrist motion resistance and grip type on CTP during wrist motion typical of occupational tasks. CTP during four wrist motion patterns, with and without resistance, and with and without gripping, was measured in vivo in 14 healthy individuals. CTP measured during compound motions fell between that measured in the cardinal planes of wrist flexion/extension and radial/ulnar deviation. Generally, with no active gripping there was little pressure change due to wrist angular displacement or resistance level. However, concurrent active pinch or power grip increased CTP particularly in motions including extension. CTP typically did not increase during wrist flexion, and in fact often decreased. Extension motions against resistance when employing a pinch or power grip increase CTP more than motions with flexion. Results could help inform design or modification of wrist motion intensive occupational tasks. © 2014 The Authors. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:524–530, 2014.